Organic electroluminescent element and electronic device thereof
Patent Information
- Application Number
- CN202280020858.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-12
- Filing Date
- 2022-03-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-03-09
AI Technical Summary
[0007]以往,提出了在覆盖层的形成中使用精细度高的金属掩模,但在高温条件下使用时存在如下问题:金属掩模因热而产生形变,由此导致位置对准精度降低
[0074]本发明的有机EL元件通过具有设置在透明电极或半透明电极的外侧且折射率比透明电极或半透明电极高的覆盖层,从而可获得能够大幅提高光取出效率的有机EL元件。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention relates to self-emissive electronic components suitable for various display devices, and more particularly to compounds and components suitable for organic electroluminescent elements (hereinafter referred to as organic EL elements). More specifically, it relates to amine compounds having a benzofuran structure or a benzothiophene structure, and organic EL elements or electronic devices obtained using the amine compounds. Background Technology
[0002] In 1987, CWTang et al. of Eastman Kodak developed a layered structure element by distributing various functions among different materials, thus putting organic EL elements using organic materials into practical use. They achieved 1000 cd / m² light emission at voltages below 10V by layering an electron-transmitting phosphor with an organic material capable of transmitting holes, and injecting both charges into the phosphor layer to induce luminescence. 2 The above high brightness (see Patent Document 1 and Patent Document 2).
[0003] To date, various improvements have been made to make organic EL elements practical, further subdividing the various functions of the stacked structure. In electroluminescent elements with an anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer, electron injection layer and cathode arranged sequentially on a substrate, high efficiency and durability are achieved by using a bottom-emitting structure that emits light from the bottom (see, for example, Non-Patent Literature 1).
[0004] In recent years, top-emitting light-emitting elements, which use a metal with a high work function as the anode and emit light from the top, have become increasingly common. In bottom-emitting structures where light is extracted from the bottom (where pixel circuitry is located), the area of the light-emitting portion is limited. In contrast, in top-emitting light-emitting elements, since light is extracted from the top, the pixel circuitry is not obstructed, thus offering the advantage of a larger light-emitting portion. In top-emitting light-emitting elements, the cathode uses semi-transparent electrodes such as LiF / Al / Ag (e.g., see Non-Patent Document 2), Ca / Mg (e.g., see Non-Patent Document 3), and LiF / MgAg.
[0005] In such light-emitting elements, if light emitted from the light-emitting layer is incident on other films at an angle greater than a certain value, total internal reflection will occur at the interface between the light-emitting layer and other films. Therefore, only a portion of the emitted light can be utilized. In recent years, to improve light extraction efficiency, light-emitting elements with a high-refractive-index "coating layer" disposed on the outside of a semi-transparent electrode with a low refractive index have been proposed (see, for example, Non-Patent Documents 2 and 3).
[0006] Regarding the effect of the capping layer in the light-emitting element with the top light-emitting structure, in a light-emitting element using Ir(ppy)3 as the light-emitting material, the current efficiency without the capping layer is 38 cd / A. In contrast, in a light-emitting element using ZnSe with a film thickness of 60 nm as the capping layer, an efficiency improvement of approximately 1.7 times (64 cd / A) was observed. Furthermore, it was shown that the maximum transmittance of the semi-transparent electrode and the capping layer does not necessarily coincide with the maximum efficiency, indicating that the maximum light extraction efficiency depends on interference effects (see, for example, Non-Patent Literature 3).
[0007] Previously, the use of high-precision metal masks in the formation of capping layers has been proposed. However, this method presents several problems when used at high temperatures: the metal mask deforms due to heat, leading to reduced alignment accuracy. Furthermore, ZnSe has a melting point exceeding 1100°C (see, for example, Non-Patent Document 3), making it impossible to deposit it at the correct position using a high-precision metal mask, potentially affecting the light-emitting element itself. Consequently, even sputtering-based film deposition can impact the light-emitting element. Therefore, capping layers using inorganic materials are unsuitable.
[0008] In addition, when using tris(8-hydroxyquinoline)aluminum (hereinafter abbreviated as Alq3) as a capping layer to adjust the refractive index (for example, refer to Non-Patent Document 2), Alq3 is known as an organic EL material that is commonly used as a green light-emitting material or an electron transport material, but it has weak absorption around 450 nm, which is used in blue light-emitting materials. Therefore, in the case of blue light-emitting elements, there are also problems of reduced color purity and reduced light extraction efficiency.
[0009] Amine compounds containing benzothiophene for use in organic EL elements have been disclosed, but these compounds are primarily used as hole transport materials (see, for example, Patent Documents 3-5).
[0010] In order to improve the characteristics of organic EL devices and to significantly improve light extraction efficiency, materials with high refractive index, low extinction coefficient, and excellent film stability and durability are sought as the coating layer.
[0011] Existing technical documents
[0012] Patent documents
[0013] Patent Document 1: Japanese Patent Application Publication No. 8-048656
[0014] Patent Document 2: Japanese Patent No. 3194657
[0015] Patent Document 3: Japanese Patent No. 4604312
[0016] Patent Document 4: Japanese Patent No. 5475450
[0017] Patent Document 5: International Publication No. 2014 / 104500
[0018] Patent Document 6: International Publication No. 2013 / 038627
[0019] Non-patent literature
[0020] Non-patent literature 1: Proceedings of the 9th Lecture of the Chinese Society of Applied Physics, pp. 55-61 (2001)
[0021] Non-patent literature 2: Appl. Phys. Let., 78, 544 (2001)
[0022] Non-patent literature 3: Appl. Phys. Let., 82, 466 (2003) Summary of the Invention
[0023] The problem the invention aims to solve
[0024] The purpose of this invention is to provide an organic EL element that has (1) high refractive index, (2) good film stability, (3) excellent durability, (4) excellent light resistance, and (5) an organic EL element having a cover layer made of a material that does not have absorption in the respective wavelength regions of blue, green and red, in order to improve the element characteristics of the organic EL element and to significantly improve the light extraction efficiency.
[0025] Physical properties of the material suitable for the capping layer in this invention include (1) high refractive index, (2) ability to be vapor-deposited, (3) stable thin film state, and (4) high glass transition temperature. Physical properties of the element suitable for this invention include (1) high light extraction efficiency, (2) no decrease in color purity, (3) light transmission without change over time, and (4) long lifespan.
[0026] Solution for solving the problem
[0027] Therefore, in order to achieve the above-mentioned objectives, the inventors focused on the excellent film stability and durability of aryl amine materials, designed amine compounds with high refractive index and specific benzofuran or benzothiophene structures, used them as materials constituting the capping layer to fabricate organic EL elements, and conducted in-depth evaluation of the characteristics of the elements, resulting in the completion of this invention.
[0028] That is, according to the present invention, the following organic EL element is provided.
[0029] 1) An organic EL element having at least an anode electrode, a hole transport layer, a light-emitting layer, an electron transport layer, a cathode electrode and a capping layer in sequence, wherein the capping layer comprises an amine compound represented by the following general formula (1) as a material.
[0030]
[0031] (In the formula, Ar1 and Ar2 may be the same or different from each other, representing the structure shown in the following general formula (A) with either R5 or R6 as the bonding site of a monovalent group. Ar3 represents the structure shown in the following general formula (A) with either R5 or R6 as the bonding site of a monovalent group, a substituted or unsubstituted aromatic hydrocarbon group, or a substituted or unsubstituted aromatic heterocyclic group. L1 and L2 may be the same or different from each other, representing a substituted or unsubstituted divalent group of an aromatic hydrocarbon with 6 to 18 cyclic carbon atoms, or a substituted or unsubstituted divalent group of an aromatic heterocyclic ring with 6 to 18 cyclic carbon atoms. L3 represents a substituted or unsubstituted divalent group of an aromatic hydrocarbon with 6 to 18 cyclic carbon atoms, a substituted or unsubstituted divalent group of an aromatic heterocyclic ring with 6 to 18 cyclic carbon atoms, or a single bond.)
[0032]
[0033] (In the formula, X represents an oxygen atom or a sulfur atom. R1 to R4 may be the same or different from each other, representing a hydrogen atom, a deuterium atom, a fluorine atom, a chlorine atom, a cyano group, a nitro group, an alkyl group with 1 to 6 carbon atoms that may have a substituent, a cycloalkyl group with 5 to 10 carbon atoms that may have a substituent, an alkenyl group with 2 to 6 carbon atoms that may have a substituent, an alkoxy group with 1 to 6 carbon atoms that may have a substituent, a cycloalkoxy group with 5 to 10 carbon atoms that may have a substituent, a substituted or unsubstituted aromatic hydrocarbon group, a substituted or unsubstituted aromatic heterocyclic group, or a substituted or unsubstituted aryloxy group. R1 to R4 bonded to the same benzene ring may be selected by...) A ring is formed by the bonding of a single bond, a substituted or unsubstituted methylene group, an oxygen atom, or a sulfur atom. Either R5 or R6 is a linking group serving as the bonding site, and it represents a hydrogen atom, a deuterium atom, a fluorine atom, a chlorine atom, a cyano group, a nitro group, an alkyl group optionally having 1 to 6 carbon atoms in a straight-chain or branched manner with a substituent, a cycloalkyl group optionally having 5 to 10 carbon atoms in a substituted manner, an alkenyl group optionally having 2 to 6 carbon atoms in a straight-chain or branched manner with a substituent, an alkoxy group optionally having 1 to 6 carbon atoms in a straight-chain or branched manner with a substituent, a cycloalkoxy group optionally having 5 to 10 carbon atoms in a substituted manner, a substituted or unsubstituted aromatic hydrocarbon group, or a substituted or unsubstituted aromatic heterocyclic group.
[0034] 2) The organic EL element according to 1) above is characterized in that the aforementioned general formula (A) is the structure shown in the following general formula (A-1).
[0035]
[0036] (In the formula, the dashed part represents the bonding area, and X, R1 to R4, and R6 are defined as in the aforementioned general formula (A).)
[0037] 3) The organic EL element according to 1) above is characterized in that the aforementioned general formula (A) is the structure shown in the following general formula (A-2).
[0038]
[0039] (In the formula, the dashed part represents the bonding area, and X, R1 to R5 are defined as in the aforementioned general formula (A).)
[0040] 4) The organic EL element according to 1) above is characterized in that L1 and L2 in the aforementioned general formula (1) are divalent groups formed by removing two hydrogen atoms from unsubstituted benzene, divalent groups formed by removing two hydrogen atoms from unsubstituted naphthalene, or divalent groups formed by removing two hydrogen atoms from unsubstituted biphenyl.
[0041] 5) The organic EL element according to 1) above is characterized in that the amine compound represented by the aforementioned general formula (1) is represented by the following general formula (1-a).
[0042]
[0043] (In the formula, X, Ar3, L3, R1~R4, R6 are defined as in the aforementioned general formula (1) and general formula (A).)
[0044] 6) The organic EL element according to 1) above, characterized in that the amine compound represented by the aforementioned general formula (1) is represented by the following general formula (1-b).
[0045]
[0046] (In the formula, X, Ar3, L3, R1 to R5 are defined as in the aforementioned general formulas (1) and (A).)
[0047] 7) An organic EL element according to any one of 1) to 6) above, wherein the thickness of the aforementioned capping layer is in the range of 30 nm to 120 nm.
[0048] 8) An organic EL element according to any one of 1) to 7) above, wherein the refractive index of the aforementioned cover layer is 1.85 or more in the range of light wavelength between 450 nm and 750 nm.
[0049] 9) An electronic device, characterized in that it comprises an organic EL element as described in any one of 1) to 8) above.
[0050] In this invention, "unsubstituted" as denoted as "substituted or unsubstituted" means that the hydrogen atom is not substituted by a substituent.
[0051] In this invention, the "substituent" used when "substituted or unsubstituted" specifically includes, but is not limited to, cyano, nitro, and halogen atoms; alkyl groups with 1 to 6 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, and n-hexyl, which are straight-chain or branched; cycloalkyl groups with 5 to 10 carbon atoms, such as cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, and adamantyl; alkenyl groups with 2 to 6 carbon atoms, such as vinyl, propenyl, 2-methylpropenyl, 1-butenyl, 2-butenyl, 3-butenyl, and 1,3-butadienyl; and methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, n-pentoxy, and n-hexoxy, which are straight-chain or branched. Straight-chain or branched alkoxy groups; cycloalkoxy groups with 5 to 10 carbon atoms, such as cyclopentoxy and cyclohexoxy; aromatic hydrocarbon groups such as phenyl, biphenyl, terphenyl, naphthyl, anthracene, phenanthryl, fluorenyl, spirodifluorenyl, indyl, pyrene, perylene, fluoranyl, and benzophenanthryl; aromatic heterocyclic groups such as pyridyl, pyrimidinyl, triazinyl, furanyl, pyrrolithyl, thiopheneyl, quinolinyl, isoquinolinyl, benzofuranyl, benzothiopheneyl, indolyl, carbazoyl, quinoxalinyl, benzimidazolyl, pyrazolyl, dibenzofuranyl, dibenzothiopheneyl, naphthidyl, phenanthrolinel, acridineyl, carbazoyl, benzoxazolyl, benzothiazoyl, and phenoxazinyl; aryloxy groups such as phenoxy and naphthoxy, which may optionally be further substituted by the aforementioned "substituents". In addition, these substituents may optionally form rings by bonding with each other via single bonds, substituted or unsubstituted methylene, oxygen or sulfur atoms.
[0052] In this invention, among the aforementioned "substituents", cyano, nitro, halogen atom, methyl, ethyl, n-propyl, methoxy, ethoxy, n-propoxy, and phenyl are preferably used.
[0053] The "aromatic hydrocarbon" in "a divalent group of an aromatic hydrocarbon with 6 to 18 cyclic carbon atoms, substituted or unsubstituted" as L1, L2, and L3 in general formula (1) specifically includes benzene, biphenyl, terphenyl, naphthalene, anthracene, phenanthrene, fluorene, etc. Furthermore, the "divalent group of an aromatic hydrocarbon" in "a divalent group of an aromatic hydrocarbon with 6 to 18 cyclic carbon atoms, substituted or unsubstituted" as L1, L2, and L3 in general formula (1) refers to a divalent group formed by removing two hydrogen atoms from the aforementioned "aromatic hydrocarbon".
[0054] Here, as the aforementioned "divalent group of aromatic hydrocarbon", it is preferred to use a divalent group (phenylene) formed by removing two hydrogen atoms from benzene, a divalent group formed by removing two hydrogen atoms from biphenyl, or a divalent group formed by removing two hydrogen atoms from naphthalene.
[0055] Furthermore, as a divalent group (phenylene) formed by removing two hydrogen atoms from benzene, it is preferable to use a divalent group (1,4-phenylene) formed by removing two hydrogen atoms at the 1,4-position of benzene, or a divalent group (1,3-phenylene) formed by removing two hydrogen atoms at the 1,3-position of benzene.
[0056] Furthermore, as a divalent group formed by removing two hydrogen atoms from biphenyl, it is preferable to use a divalent group formed by removing two hydrogen atoms at the 4,4'-position of biphenyl.
[0057] Furthermore, as a divalent group formed by removing two hydrogen atoms from naphthalene, it is preferable to use a divalent group formed by removing two hydrogen atoms at the 1,4-position of naphthalene, or a divalent group formed by removing two hydrogen atoms at the 2,7-position of naphthalene.
[0058] In addition, in this invention, it is preferred to use L3 as a single bond.
[0059] The "aromatic heterocycle" in "a divalent group of an aromatic heterocycle with 6 to 18 cyclic atoms, substituted or unsubstituted" as shown in general formula (1) can be pyridine, pyrimidine, quinoline, benzofuran, benzothiophene, benzoxazole, benzothiazole, dibenzofuran, dibenzothiophene, phenanthroline, etc. Furthermore, the "divalent group of an aromatic heterocycle" in "a divalent group of an aromatic heterocycle with 6 to 18 cyclic atoms, substituted or unsubstituted" as shown in general formula (1) refers to a divalent group formed by removing two hydrogen atoms from the aforementioned "aromatic heterocycle".
[0060] As for the "substituted or unsubstituted aromatic hydrocarbon groups" represented by Ar3 in general formula (1) and R1 to R6 in general formula (A), specifically, phenyl, biphenyl, terphenyl, naphthyl, anthracene, phenanthryl, fluorenyl, spirodifluorenyl, indyl, pyrene, perylene, fluoranyl, benzophenanthryl, etc.
[0061] Here, the "aromatic hydrocarbon group" in "substituted or unsubstituted aromatic hydrocarbon group" shown in Ar3 above is preferably phenyl, biphenyl, terphenyl, naphthyl or phenanthrene.
[0062] As for the "substituted or unsubstituted aromatic heterocyclic group" represented by Ar3 in general formula (1) and R1 to R6 in general formula (A), specifically, pyridyl, pyrimidinyl, triazinyl, furanyl, pyrrolithyl, thiopheneyl, quinolinyl, isoquinolinyl, benzofuranyl, benzothiopheneyl, indolyl, carbazoyl, quinoxalinyl, benzimidazolyl, pyrazolyl, dibenzofuranyl, dibenzothiopheneyl, naphridinyl, phenanthrololinyl, acridineyl, carbazoyl, benzoxazolyl, benzothiazoyl, phenoxazinyl, etc.
[0063] Here, the "aromatic heterocyclic group" in the "substituted or unsubstituted aromatic heterocyclic group" shown in Ar3 above is preferably quinolinyl, isoquinolinyl, benzofuranyl, benzothiophenyl, dibenzofuranyl, dibenzothiophenyl, benzoxazolyl or benzothiazolyl.
[0064] The "alkyl" in R1 to R6 of general formula (A), which refers to "a straight-chain or branched alkyl group having 1 to 6 carbon atoms with substituents", specifically includes methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, etc.
[0065] The "cycloalkyl group" in general formula (A) that is "optionally a cycloalkyl group with 5 to 10 carbon atoms having a substituent" as R1 to R6 can specifically include cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, adamantyl, etc.
[0066] The "alkenyl" in R1 to R6 of general formula (A), which refers to "alkenyl groups of 2 to 6 carbon atoms of any type with substituents, either straight-chain or branched," can specifically include vinyl, propenyl, 2-methylpropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1,3-butadienyl, etc.
[0067] The "alkoxy group" in general formula (A) that is "a straight-chain or branched alkoxy group having 1 to 6 carbon atoms with substituents" as R1 to R6 can specifically include methoxy, ethoxy, propoxy, isopropoxy, butoxy, pentoxy, hexoxy, etc.
[0068] The "cycloalkoxy group" in "a cycloalkoxy group with 5 to 10 carbon atoms that may have a substituent" as R1 to R6 in general formula (A) can specifically include cyclopentoxy, cyclohexoxy, etc.
[0069] As "aryloxy group" in "substituted or unsubstituted aryloxy group" represented by R1 to R4 in general formula (A), specifically, phenoxy, naphthoxy, etc. can be listed.
[0070] In the organic EL element of the present invention, the thickness of the aforementioned capping layer is preferably in the range of 30 nm to 120 nm, and more preferably in the range of 40 nm to 80 nm.
[0071] In the organic EL element of the present invention, the refractive index of the aforementioned cover layer is preferably 1.85 or more, more preferably 1.88 or more, and even more preferably 1.92 or more, in which the wavelength of light transmitted through the aforementioned cover layer is in the range of 450 nm or more and 750 nm or less.
[0072] In addition, in the organic EL element of the present invention, the aforementioned cover layer can be made by laminating two or more different constituent materials or by forming a mixed layer. In this case, the constituent materials preferably include two or more different compounds selected from the amine compounds of the aforementioned general formula (1) suitable for use in the organic EL element of the present invention.
[0073] The effects of the invention
[0074] The organic EL element of the present invention has a cover layer disposed outside the transparent electrode or the semi-transparent electrode and having a higher refractive index than the transparent electrode or the semi-transparent electrode, thereby obtaining an organic EL element that can significantly improve light extraction efficiency. Attached Figure Description
[0075] Figure 1 The diagram shows the structural formulas of compounds (1-1) to (1-15) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0076] Figure 2 The diagram shows the structural formulas of compounds (1-16) to (1-30) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0077] Figure 3 The diagram shows the structural formulas of compounds (1-31) to (1-45) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0078] Figure 4 The diagram shows the structural formulas of compounds (1-46) to (1-60) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0079] Figure 5 The diagram shows the structural formulas of compounds (1-61) to (1-75) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0080] Figure 6The diagram shows the structural formulas of compounds (1-76) to (1-90) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0081] Figure 7 The diagram shows the structural formulas of compounds (1-91) to (1-105) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0082] Figure 8 The diagram shows the structural formulas of compounds (1-106) to (1-120) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0083] Figure 9 The diagram shows the structural formulas of compounds (1-121) to (1-135) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0084] Figure 10 The diagram shows the structural formulas of compounds (1-136) to (1-150) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0085] Figure 11 The diagram shows the structural formulas of compounds (1-151) to (1-165) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0086] Figure 12 The diagram shows the structural formulas of compounds (1-166) to (1-180) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0087] Figure 13 The diagram shows the structural formulas of compounds (1-181) to (1-195) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0088] Figure 14 The diagram shows the structural formulas of compounds (1-196) to (1-210) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0089] Figure 15 The diagram shows the structural formulas of compounds (1-211) to (1-218) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0090] Figure 16The diagram shows the structural formulas of compounds (1-219) to (1-224) as amine compounds of general formula (1) suitable for use in the organic EL element of the present invention.
[0091] Figure 17 This is a diagram showing the structural formula of compound (1-225) as an amine compound of general formula (1) suitable for use in the organic EL element of the present invention.
[0092] Figure 18 This is a diagram showing the configuration of the organic EL elements in Examples 38-70 and Comparative Examples 1-2. Detailed Implementation
[0093] Regarding the amine compound represented by the aforementioned general formula (1) suitable for use in the organic EL element of the present invention, it can be synthesized by known methods (for example, see Patent Document 4).
[0094] Specific examples of amine compounds of the aforementioned general formula (1) suitable for use in the organic EL element of the present invention are shown in Figures 1 to 17 However, it is not limited to these compounds.
[0095] The method for manufacturing the amine compound represented by the aforementioned general formula (1) suitable for use in the organic EL element of the present invention is not particularly limited. The compound can be purified by known methods for purifying organic compounds, such as column chromatography purification, adsorption purification based on silica gel, activated carbon, activated clay, etc., solvent-based recrystallization, crystallization, etc., and finally purified by sublimation purification, etc. The compound can be identified by NMR analysis, etc. As physical properties, it is preferable to measure the melting point, glass transition temperature (Tg), refractive index, and extinction coefficient.
[0096] Melting point and glass transition temperature (Tg) can be determined, for example, using powder and employing a high-sensitivity differential scanning calorimeter (Bruker AXS KK, DSC3100SA).
[0097] The refractive index and extinction coefficient can be measured by fabricating an 80 nm thin film on a silicon substrate and using a spectrophotometer (FILMETRICS F10-RT-UV).
[0098] As for the structure of the organic EL element of the present invention, for example, in the case of a top-emitting structure light-emitting element, the following structures can be listed: a structure that sequentially includes an anode, a hole transport layer, a light-emitting layer, an electron transport layer, a cathode, and a capping layer on a glass substrate; a structure that has a hole injection layer between the anode and the hole transport layer; a structure that has an electron blocking layer between the hole transport layer and the light-emitting layer; a structure that has a hole blocking layer between the light-emitting layer and the electron transport layer; and a structure that has an electron injection layer between the electron transport layer and the cathode. In these multilayer structures, some organic layers can be omitted or used in combination. For example, it is also possible to make a structure that combines a hole injection layer and a hole transport layer, a structure that combines a hole transport layer and an electron blocking layer, a structure that combines a hole blocking layer and an electron transport layer, and a structure that combines an electron transport layer and an electron injection layer, etc. In addition, it is also possible to make a structure by stacking two or more organic layers with the same function, and it is also possible to make a structure by stacking two hole transport layers, a structure by stacking two light-emitting layers, a structure by stacking two electron transport layers, a structure by stacking two capping layers, etc.
[0099] The total film thickness of all layers in the organic EL element is preferably around 200 nm to 750 nm, more preferably around 350 nm to 600 nm. Furthermore, the thickness of the capping layer is preferably, for example, 30 nm to 120 nm, more preferably 40 nm to 80 nm. In this case, good light extraction efficiency can be obtained. It should be noted that the thickness of the capping layer can be appropriately varied depending on the type of light-emitting material used in the light-emitting element and the thickness of each layer of the organic EL element other than the capping layer.
[0100] As the anode of the organic EL element of the present invention, electrode materials with high work functions such as ITO and gold can be used.
[0101] As the hole injection layer of the organic EL element of the present invention, it is preferably an arylamine compound having a structure in which two or more triphenylamine structures are linked by single bonds or divalent groups without heteroatoms in the molecule. Examples include benzidine derivatives, star-shaped triphenylamine derivatives, and various triphenylamine tetramers. Additionally, porphyrin compounds represented by copper phthalocyanine, acceptor heterocyclic compounds such as hexacyanoazinebenzophenanthrene, and coating polymers can be used. These materials can be used individually as films, or as monolayers formed by mixing with other materials. They can also be fabricated into stacked structures of individually formed layers, stacked structures of mixed layers, or stacked structures of individually formed layers and mixed layers. Besides vapor deposition, these materials can also be used to form thin films using known methods such as spin coating and inkjet printing.
[0102] As the hole transport layer of the organic EL element of the present invention, benzidine derivatives such as N,N'-diphenyl-N,N'-di(m-tolyl)benzidine (TPD), N,N'-diphenyl-N,N'-di(α-naphthyl)benzidine (NPD), and N,N,N',N'-tetraphenylbenzidine are preferably used; 1,1-bis[4-(di-4-tolylamino)phenyl]cyclohexane (TAPC); and especially arylamine compounds having a structure in which two triphenylamine structures are linked by single bonds or divalent groups without heteroatoms, such as N,N,N',N'-tetraphenylbenzidine. Furthermore, arylamine compounds having only one triphenylamine structure in the molecule, or arylamine compounds having a structure in which three or more triphenylamine structures are linked by single bonds or divalent groups without heteroatoms, such as various triphenylamine trimers and tetramers, are preferred. These materials can be used individually as films, or as monolayers formed by mixing with other materials. They can also be used to create stacked structures of individually formed layers, stacked structures of mixed layers, or stacked structures of individually formed layers and mixed layers. Furthermore, coating polymers such as poly(3,4-ethylenedioxythiophene) (PEDOT) / poly(styrene sulfonate) (PSS) can be used as hole injection / delivery layers. These materials can be used for thin film formation using known methods such as spin coating and inkjet printing, in addition to vapor deposition.
[0103] Furthermore, in the hole injection layer or hole transport layer, it is preferable to further p-dop the material commonly used in this layer with antimony hexachloride tribromophenylamine, axial alkene derivatives, etc. Alternatively, polymeric compounds having structures containing benzidine derivatives such as TPD in part of their structure can be used.
[0104] As the electron blocking layer of the organic EL element of the present invention, carbazole derivatives such as 4,4',4”-tris(N-carbazole)triphenylamine (TCTA), 9,9-bis[4-(carbazole-9-yl)phenyl]fluorene, 1,3-bis(carbazole-9-yl)phenyl (mCP), and 2,2-bis(4-carbazole-9-yl-phenyl)adamantane (Ad-Cz) can be used; 9-[4-(carbazole-9-yl)phenyl]-9-[4-(triphenylsilyl)phenyl]-9H-fluorene These are compounds with electron-blocking properties, such as those with triphenylsilyl and triarylamine structures. They can be used alone as films, or as monolayers formed by mixing with other materials. They can also be used to form stacked structures of individually formed layers, stacked structures of mixed layers, or stacked structures of individually formed layers and mixed layers. In addition to vapor deposition, these materials can also be used to form thin films using known methods such as spin coating and inkjet printing.
[0105] As the light-emitting layer of the organic EL element of the present invention, in addition to metal complexes of hydroxyquinoline derivatives, primarily Alq3, various metal complexes, anthracene derivatives, bis(styrene)benzene derivatives, pyrene derivatives, oxazole derivatives, poly(p-phenylene)ethylene derivatives, etc., can also be used. Furthermore, the light-emitting layer can be composed of a host material and a dopant material. As the host material, anthracene derivatives are preferred. In addition to using the aforementioned light-emitting materials, heterocyclic compounds with a partial structure having an indole ring as a fused ring, heterocyclic compounds with a partial structure having a carbazole ring as a fused ring, carbazole derivatives, thiazole derivatives, benzimidazole derivatives, polydialkylfluorene derivatives, etc., can also be used. Furthermore, as dopant materials, quinacridone, coumarin, rubrene, perylene and their derivatives, benzopyran derivatives, rhodamine derivatives, aminostyrene derivatives, etc., can be used. They can be used as individual films, or as monolayers obtained by mixing with other materials to form films. They can also be made into stacked structures of individual film layers, stacked structures of mixed film layers, or stacked structures of individual film layers and mixed film layers.
[0106] In addition, phosphorescent materials can also be used as luminescent materials. Phosphorescent materials composed of metal complexes such as iridium and platinum can be used. Green phosphorescent materials such as Ir(ppy)3, blue phosphorescent materials such as Firpic and Fir6, and red phosphorescent materials such as Btp2Ir(acac) can be used. As the host material, for hole injection / transport, carbazole derivatives such as 4,4'-bis(N-carbazolyl)biphenyl (CBP), TCTA, and mCP can be used. For electron transport, materials such as p-bis(triphenylsilyl)benzene (UGH2) and 2,2',2”-(1,3,5-phenylene)-tris(1-phenyl-1H-benzimidazole) (TPBI) can be used, enabling the fabrication of high-performance organic EL devices.
[0107] To avoid concentration quenching, the phosphorescent luminescent material is preferably doped in the host material at a rate of 1 to 30% by weight relative to the total luminescent layer by co-evaporation.
[0108] In addition, materials that emit delayed fluorescence can also be used as luminescent materials. Besides vapor deposition, these materials can also be formed into thin films using known methods such as spin coating and inkjet printing.
[0109] As the hole-blocking layer for the organic EL element of this invention, compounds with hole-blocking properties, such as phenanthroline derivatives like copper bath (BCP), metal complexes of hydroxyquinoline derivatives like bis(2-methyl-8-hydroxyquinoline)-4-phenylphenol aluminum(III) (BAlq), various rare earth complexes, triazole derivatives, triazine derivatives, pyrimidine derivatives, oxadiazole derivatives, and benzo[a]azole derivatives, can be used. These materials can also serve as electron transport layers. They can be formed individually or as monolayers mixed with other materials, or in stacked structures of individually formed layers, mixed layers, or a combination of individually formed and mixed layers. Besides vapor deposition, these materials can also be formed into thin films using known methods such as spin coating and inkjet printing.
[0110] As the electron transport layer of the organic EL element of this invention, in addition to metal complexes of hydroxyquinoline derivatives, primarily Alq3 and Balq, various metal complexes, triazole derivatives, triazine derivatives, pyrimidine derivatives, oxadiazole derivatives, pyridine derivatives, benzimidazole derivatives, benzoxazole derivatives, thiadiazole derivatives, anthracene derivatives, carbodiimide derivatives, quinoxaline derivatives, pyridoindole derivatives, phenanthroline derivatives, silole derivatives, etc., can be used as individual films or as monolayers obtained by mixing with other materials. They can also be used to form stacked structures of individually formed layers, stacked structures of mixed layers, or stacked structures of individually formed layers and mixed layers. Besides vapor deposition, these materials can also be used to form thin films using known methods such as spin coating and inkjet printing.
[0111] As the electron injection layer of the organic EL element of the present invention, alkali metal salts such as lithium fluoride and cesium fluoride; alkaline earth metal salts such as magnesium fluoride; metal complexes of hydroxyquinoline derivatives such as lithium hydroxyquinoline; metal oxides such as aluminum oxide; or metals such as ytterbium (Yb), samarium (Sm), calcium (Ca), strontium (Sr), and cesium (Cs) can be used. In the preferred selection of the electron transport layer and the cathode, these can be omitted.
[0112] Furthermore, in the electron injection layer or electron transport layer, a material obtained by further n-doping a material commonly used in that layer with metals such as cesium can be used.
[0113] As the cathode of the organic EL element of the present invention, electrode materials with low work function such as aluminum, alloys with even lower work function such as magnesium-silver alloys, magnesium-calcium alloys, magnesium-indium alloys, aluminum-magnesium alloys, ITO, IZO, etc. are used as electrode materials.
[0114] As the capping layer for the organic EL element of the present invention, amine compounds represented by the aforementioned general formulas (1), (1-a), or (1-b) are preferably used. In addition to vapor deposition, these materials can also be used to form thin films using known methods such as spin coating and inkjet printing.
[0115] As an amine compound of the aforementioned general formula (1), (1-a) or (1-b) suitable for use in the organic EL element of the present invention, the refractive index is preferably 1.85 or more, more preferably 1.88 or more, and even more preferably 1.92 or more in the range of wavelength 450 nm or more and 750 nm or less.
[0116] It should be noted that the above description refers to organic EL elements with a top-emitting structure, but the present invention is not limited thereto. It can also be applied to organic EL elements with a bottom-emitting structure, and organic EL elements with a dual-emitting structure that emits light from both the top and bottom. In these cases, the electrode located in the direction from which light is emitted from the light-emitting element needs to be transparent or semi-transparent.
[0117] Example
[0118] The following describes specific embodiments of the present invention through examples, but the present invention is not limited to the following examples as long as it does not depart from its spirit.
[0119] [Example 1]
[0120] Synthesis of Compounds (1-10)
[0121] 147 g of 1-bromo-4-iodobenzene, 61.6 g of 2-benzothiophene boric acid, 600 mL of toluene, 200 mL of ethanol, and an aqueous solution obtained by dissolving 71.7 g of potassium carbonate in 260 mL of purified water were added to a nitrogen-purged reaction vessel. Nitrogen gas was then introduced for 30 minutes. 4.0 g of tetra(triphenylphosphine)palladium was added, and the mixture was stirred under reflux for 14 hours. After cooling to room temperature, the organic layer was collected by separation of the reaction mixture. The resulting organic layer was heated, and 50 g of silica gel was added at 80 °C, followed by stirring for 1 hour. The silica gel was removed by hot filtration, and the filtrate was concentrated. 300 mL of heptane was added to the residue, and the mixture was stirred at room temperature for 1 hour. The resulting solid was collected by filtration to give 54.8 g of a yellowish-white powder of 2-(4-bromophenyl)benzothiophene (yield: 54.8%).
[0122] 18.0 g of the obtained 2-(4-bromophenyl)benzothiophene, 7.6 g of 4-(9-phenanthrene)aniline, 180 mL of toluene, and 10.2 g of sodium tert-butoxide were added to a reaction vessel purged with nitrogen, and nitrogen was purged for 30 minutes. 0.5 g of tris(dibenzylacetone)palladium and 2.2 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added, and the mixture was stirred under reflux for 8 hours. After cooling to room temperature, 90 mL of methanol was added, and the precipitated solid was collected by filtration. 80 mL of methanol and 80 mL of water were added to the obtained solid, and the mixture was stirred under reflux for 1 hour. The solid was collected by filtration, and 400 mL of chlorobenzene was added. The mixture was heated to 100°C to dissolve the solid. 8 g of silica gel and 8 g of activated clay were added, and the mixture was stirred for 1 hour. The solid was removed by hot filtration, and the resulting filtrate was concentrated. 180 mL of methanol was added to the residue and stirred under reflux for 1 hour to obtain 10.5 g of yellow powder of compound (1-10) (yield: 54.1%).
[0123]
[0124] The structure of the obtained yellow powder was identified using NMR.
[0125] use 1 H-NMR (THF-d8) detected the signals of the following 31 hydrogen atoms.
[0126] δ(ppm)=8.80-8.93(2H), 8.08-8.10(1H), 7.96-7.98(1H), 7.86-7.88(2H), 7.57-7.81(15H), 7.29-7.40(10H).
[0127] [Example 2]
[0128] Synthesis of Compounds (1-34)
[0129] In Example 1, 4-(9-phenanthroline)aniline was replaced with 4-(3-dibenzofuranyl)aniline, and the same operation was performed to obtain 9.7 g of yellow powder of compound (1-34) (yield: 53%).
[0130]
[0131] The structure of the obtained yellow powder was identified using NMR.
[0132] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0133] δ(ppm)=7.94-7.98(2H), 7.73-7.79(5H), 7.56-7.64(8H), 7.43-7.47(3H), 7.16-7.36(11H).
[0134] [Example 3]
[0135] Synthesis of Compounds (1-7)
[0136] In Example 1, 4-(9-phenanthyl)aniline was replaced with 4-amino-p-terphenyl, and the same operation was performed to obtain 7.5 g of yellow powder of compounds (1-7) (yield: 93%).
[0137]
[0138] The structure of the obtained yellow powder was identified using NMR.
[0139] use 1 H-NMR (CDCl3) detected the following 31 hydrogen signals.
[0140] δ(ppm)=7.81(2H), 7.75(2H), 7.67(4H), 7.66-7.63(6H), 7.59(2H), 7.48-7.44(4H), 7.38-7.24(7H), 7.21(4H).
[0141] [Example 4]
[0142] Synthesis of Compounds (1-29)
[0143] In Example 1, 4-(9-phenanthyl)aniline was replaced with 4-(2-benzothiazolyl)aniline, and the same operation was performed to obtain 10.4 g of yellow powder of compound (1-29) (yield: 61%).
[0144]
[0145] The structure of the obtained yellow powder was identified using NMR.
[0146] use 1 H-NMR (CDCl3) detected the signals of the following 26 hydrogen atoms.
[0147] δ(ppm)=8.04(1H), 8.00(2H), 7.89(1H), 7.28(2H), 7.77(2H), 7.66(4H), 7.51(2H), 7.48(1H), 7.40-7.28(5H), 7.27-7.21(6H).
[0148] [Example 5]
[0149] Synthesis of Compounds (1-32)
[0150] In Example 1, 4-(9-phenanthroline)aniline was replaced with 4-(1-dibenzofuranyl)aniline, and the reaction was carried out in the same manner. After collecting the solid, it was purified by crystallization with tetrahydrofuran and acetone to obtain 5.1 g of yellow powder of compound (1-32) (yield: 65%).
[0151]
[0152] The structure of the obtained yellow powder was identified using NMR.
[0153] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0154] δ(ppm)=7.82(2H), 7.77(2H), 7.72(1H), 7.68(4H), 7.60-7.56(4H), 7.52-7.48(3H), 7.44(1H), 7.37-7.28(11H), 7.22(1H).
[0155] [Example 6]
[0156] Synthesis of Compounds (1-33)
[0157] In Example 1, 4-(9-phenanthroline)aniline was replaced with 4-(2-dibenzofuranyl)aniline, and the same reaction was carried out. After collecting the solid, it was purified by crystallization with tetrahydrofuran and acetone to obtain 10.2 g of a yellow powder of compound (1-33) (yield: 66%).
[0158]
[0159] The structure of the obtained yellow powder was identified using NMR.
[0160] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0161] δ(ppm)=8.16(1H), 8.01(1H), 7.82(2H), 7.76(2H), 7.71-7.59(9H), 7.51-7.47(3H), 7.39-7.28(7H), 7.23(4H).
[0162] [Example 7]
[0163] Synthesis of Compounds (1-35)
[0164] In Example 1, 4-(9-phenanthroline)aniline was replaced with 4-(4-dibenzofuranyl)aniline, and the same reaction was carried out. After collecting the solid, it was purified by crystallization with tetrahydrofuran and acetone to obtain 11.1 g of a yellow powder of compound (1-35) (yield: 66%).
[0165]
[0166] The structure of the obtained yellow powder was identified using NMR.
[0167] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0168] δ(ppm)=8.00(1H), 7.93(1H), 7.91(2H), 7.83(2H), 7.77(2H), 7.67(4H), 7.63(2H), 7.50(2H), 7.48-7.42(2H), 7.39-7.26(11H).
[0169] [Example 8]
[0170] Synthesis of Compounds (1-37)
[0171] In Example 1, 4-(9-phenanthyl)aniline was replaced with 4-(2-dibenzothiophene)aniline, and the same reaction was carried out. After collecting the solid, it was purified by crystallization with tetrahydrofuran and acetone to obtain 10.2 g of a yellow powder of compound (1-37) (yield: 45%).
[0172]
[0173] The structure of the obtained yellow powder was identified using NMR.
[0174] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0175] δ(ppm)=8.36(1H), 8.23(1H), 7.92(1H), 7.88(1H), 7.83(2H), 7.77(2H), 7.71(1H), 7.68-7.65(6H), 7.52-7.48(5H), 7.38-7.23(9H)
[0176] [Example 9]
[0177] Synthesis of Compounds (1-39)
[0178] In Example 1, 4-(9-phenanthyl)aniline was replaced with 4-(4-dibenzothiophene)aniline, and the same operation was performed to obtain 6.6 g of yellow powder of compound (1-39) (yield: 88%).
[0179]
[0180] The structure of the obtained yellow powder was identified using NMR.
[0181] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0182] δ(ppm)=8.20(1H), 8.16(1H), 7.86(1H), 7.83(2H), 7.77(2H), 7.71(2H), 7.67(4H), 7.57(1H), 7.53-7.47(5H), 7.37-7.26(10H).
[0183] [Example 10]
[0184] Synthesis of Compounds (1-87)
[0185] In Example 1, 4-(9-phenanthyl)aniline was replaced with 4-(4-dibenzothiophene)naphth-1-yl-amine, and the same reaction was carried out. After collecting the solid, it was purified by crystallization using a mixed solvent of toluene / acetone, thereby giving 6.6 g of a yellow powder of compound (1-87) (yield: 64%).
[0186]
[0187] The structure of the obtained yellow powder was identified using NMR.
[0188] use 1 H-NMR (CDCl3) detected the following 31 hydrogen signals.
[0189] δ(ppm)=8.28(1H), 8.25(1H), 8.08(1H), 7.81(2H), 7.78(1H), 7.76-7.72(3H), 7.68(1H) , 7.66-7.62(5H), 7.57(1H), 7.53-7.50(2H), 7.49-7.44(4H), 7.42-7.26(5H), 7.21(4H).
[0190] [Example 11]
[0191] Synthesis of Compounds (1-95)
[0192] 4.5 g of 4-(2-naphthyl)aniline, 68 mL of xylene, 14.6 g of 2-(7-bromonaphthyl-2-yl)benzothiophene, 4.9 g of sodium tert-butoxide, 0.2 g of tris(dibenzylacetone)dipalladium, and 0.2 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added to a nitrogen-purified reaction vessel, and the mixture was stirred under reflux overnight. After cooling to room temperature, methanol was added, and the solid was collected by filtration. The resulting solid was purified by crystallization using a mixed solvent of chlorobenzene / acetone to give 2.9 g of a yellow powder of compound (1-95) (yield: 19%).
[0193]
[0194] The structure of the obtained yellow powder was identified using NMR.
[0195] use 1 H-NMR (CDCl3) detected the following 33 hydrogen signals.
[0196] δ(ppm)=8.17(2H), 7.96(2H), 7.91-7.73(13H), 7.65(4H), 7.57(1H), 7.40(2H), 7.38-7.27(9H).
[0197] [Example 12]
[0198] Synthesis of Compounds (1-96)
[0199] In Example 11, 4-(2-naphthyl)aniline was replaced with 4-(2-benzoxazolyl)aniline, and the same operation was performed to obtain 5.5 g of yellow powder of compound (1-96) (yield: 35%).
[0200]
[0201] The structure of the obtained yellow powder was identified using NMR.
[0202] use 1 H-NMR (CDCl3) detected the signals of the following 30 hydrogen atoms.
[0203] δ(ppm)=8.07(1H), 7.95(2H), 7.94-7.74(13H), 7.70(2H), 7.64(2H), 7.62(1H), 7.50(2H), 7.42(2H), 7.38-7.27(5H).
[0204] [Example 13]
[0205] <Synthesis of Compound (1-211)>
[0206] In Example 11, 4-(2-naphthyl)aniline was replaced with 4-(3-dibenzofuranyl)aniline, and the same operation was performed to obtain 8.9 g of yellow powder of compound (1-211) (yield: 74%).
[0207]
[0208] The structure of the obtained yellow powder was identified using NMR.
[0209] use 1 H-NMR (CDCl3) detected the following 33 hydrogen signals.
[0210] δ(ppm)=8.00(1H), 7.97(1H), 7.95(2H), 7.83(6H), 7.77(5H), 7.64(7H), 7.79(1H), 7.46(1H), 7.42(2H), 7.39-7.27(7H).
[0211] [Example 14]
[0212] Synthesis of Compound (1-152)
[0213] 5.0 g of 4-(2-naphthyl)aniline, 100 mL of toluene, 13.7 g of 2-(4-bromophenyl)benzofuran, 6.6 g of sodium tert-butoxide, 0.8 g of tris(dibenzylacetone)dipalladium, and 0.8 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added to a nitrogen-purified reaction vessel, and the mixture was stirred under reflux overnight. After cooling to room temperature, methanol was added, and the solid was collected by filtration. The resulting solid was purified by crystallization using tetrahydrofuran and acetone to give 8.2 g of a yellow powder of compound (1-152) (yield: 53%).
[0214]
[0215] The structure of the obtained yellow powder was identified using NMR.
[0216] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0217] δ(ppm)=8.05(1H), 7.90(2H), 7.86(1H), 7.79(4H), 7.76(1H), 7.68(2H), 7.57(2H), 7.52(2H), 7.49(2H), 7.32-7.19(10H), 6.95(2H).
[0218] [Example 15]
[0219] Synthesis of Compound (1-153)
[0220] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(9-phenanthyl)aniline, and the same operation was performed to obtain 3.4 g of yellow powder of compound (1-153) (yield: 31%).
[0221]
[0222] The structure of the obtained yellow powder was identified using NMR.
[0223] use 1 H-NMR (CDCl3) detected the following 31 hydrogen signals.
[0224] δ(ppm)=8.80(1H), 8.74(1H), 8.07(1H), 7.92(1H), 7.83(4H), 7.75(1H), 7.73-7.58(6H), 7.54-7.51(4H), 7.34-7.22(10H), 6.97(2H).
[0225] [Example 16]
[0226] Synthesis of Compound (1-154)
[0227] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(2-benzoxazolyl)aniline, and the same reaction was carried out. After collecting the solid, it was purified by crystallization using a mixed solvent of chlorobenzene / acetone, thereby giving 10.7 g of a yellow powder of compound (1-154) (yield: 75%).
[0228]
[0229] The structure of the obtained yellow powder was identified using NMR.
[0230] use 1 H-NMR (CDCl3) detected the signals of the following 26 hydrogen atoms.
[0231] δ (ppm)=8.15(2H), 7.83(4H), 7.76(1H), 7.58(3H), 7.52(2H), 7.34(2H), 7.32-7.21(10H), 6.99(2H).
[0232] [Example 17]
[0233] Synthesis of Compounds (1-158)
[0234] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(2-dibenzofuranyl)aniline, and the same operation was performed to obtain 3.8 g of yellow powder of compound (1-158) (yield: 31%).
[0235]
[0236] The structure of the obtained yellow powder was identified using NMR.
[0237] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0238] δ(ppm)=8.16(1H), 8.01(1H), 7.79(4H), 7.70(1H), 7.64-7.57(6H), 7.53-7.47(3H), 7.38(1H), 7.30-7.21(10H), 6.96(2H).
[0239] [Example 18]
[0240] Synthesis of Compounds (1-160)
[0241] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(2-dibenzothiophene)aniline, and the same operation was performed to obtain 6.7 g of yellow powder of compound (1-160) (yield: 40%).
[0242]
[0243] The structure of the obtained yellow powder was identified using NMR.
[0244] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0245] δ(ppm)=8.36(1H), 8.22(1H), 7.91(1H), 7.87(1H), 7.79(4H), 7.70(1H) , 7.66(1H), 7.57(2H), 7.52(2H), 7.48(2H), 7.30-7.21(11H), 6.95(2H).
[0246] [Example 19]
[0247] Synthesis of Compound (1-161)
[0248] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(4-dibenzothiophene)aniline, and the same operation was performed to obtain 4.5 g of yellow powder of compound (1-161) (yield: 42%).
[0249]
[0250] The structure of the obtained yellow powder was identified using NMR.
[0251] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0252] δ(ppm)=8.20(1H), 8.15(1H), 7.86(1H), 7.81(4H), 7.71(2H), 7.58-7.51(6H), 7.47(2H), 7.33-7.21(10H), 6.96(2H).
[0253] [Example 20]
[0254] Synthesis of Compound (1-166)
[0255] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(3-quinolinyl)aniline, and the same operation was performed to obtain 10.7 g of yellow powder of compound (1-166) (yield: 75%).
[0256]
[0257] The structure of the obtained yellow powder was identified using NMR.
[0258] use 1 H-NMR (CDCl3) detected the signals of the following 28 hydrogen atoms.
[0259] δ(ppm)=9.21(1H), 8.30(1H), 8.14(1H), 7.89(1H), 7.80(4H), 7.72(1H), 7.6 7(2H), 7.58(1H), 7.57(2H), 7.52(2H), 7.32(2H), 7.31-7.20(8H), 6.96(2H).
[0260] [Example 21]
[0261] <Synthesis of Compound (1-212)>
[0262] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-amino-p-terphenyl, and the same operation was performed to obtain 9.2 g of yellow powder of compound (1-212) (yield: 60%).
[0263]
[0264] The structure of the obtained yellow powder was identified using NMR.
[0265] use 1 H-NMR (CDCl3) detected the following 31 hydrogen signals.
[0266] δ(ppm)=7.79(4H), 7.68(4H), 7.65(2H), 7.59(4H), 7.51(2H), 7.47(2H), 7.36(1H), 7.29-7.21(10H), 6.95(2H).
[0267] [Example 22]
[0268] <Synthesis of Compound (1-213)>
[0269] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(3-dibenzofuranyl)aniline, and the same operation was performed to obtain 5.1 g of yellow powder of compound (1-213) (yield: 52%).
[0270]
[0271] The structure of the obtained yellow powder was identified using NMR.
[0272] use 1 H-NMR (CDCl3) detected the signals of the following 29 hydrogen atoms.
[0273] δ(ppm)=8.00(1H), 7.97(1H), 7.81-7.79(5H), 7.66-7.57(6H), 7.52(2H), 7.47(1H), 7.37(1H), 7.30-7.21(10H), 6.96(2H).
[0274] [Example 23]
[0275] <Synthesis of Compound (1-214)>
[0276] In Example 14, 4-(2-naphthyl)aniline was replaced with 4'-benzofuran-2-yl-biphenyl-4-yl-amine, and the same operation was performed to obtain 11.4 g of pale yellow powder of compound (1-214) (yield: 81%).
[0277]
[0278] The structure of the obtained pale yellow powder was identified using NMR.
[0279] use 1 H-NMR (CDCl3) detected the following 31 hydrogen signals.
[0280] δ(ppm)=7.95(2H), 7.80(4H), 7.70(2H), 7.62-7.51(8H), 7.34-7.21(12H), 7.07(1H), 6.96(2H).
[0281] [Example 24]
[0282] <Synthesis of Compound (1-215)>
[0283] In Example 14, 4-(2-naphthyl)aniline was replaced with 4'-benzoxazol-2-yl-biphenyl-4-yl-amine, and the same operation was performed to obtain 7.2 g of yellow powder of compound (1-215) (yield: 72%).
[0284]
[0285] The structure of the obtained yellow powder was identified using NMR.
[0286] 1 H-NMR (CDCl3) detected the signals of the following 30 hydrogen atoms.
[0287] Using δ(ppm) = 8.33(2H), 7.81-7.76(7H), 7.64-7.51(7H), 7.38-7.36(2H), 7.30-7.21(10H), 6.96(2H).
[0288] [Example 25]
[0289] <Synthesis of Compound (1-216)>
[0290] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(2-phenyl-benzoxazol-6-yl)aniline, and the same reaction was carried out. After collecting the solid, it was purified by recrystallization with chlorobenzene to obtain 14.3 g of a yellow powder of compound (1-216) (yield: 70%).
[0291]
[0292] The structure of the obtained yellow powder was identified using NMR.
[0293] use 1 H-NMR (CDCl3) detected the signals of the following 30 hydrogen atoms.
[0294] δ(ppm)=8.28(2H), 7.80(6H), 7.65-7.54(8H), 7.52(2H), 7.31-7.20(10H), 6.96(2H).
[0295] [Example 26]
[0296] <Synthesis of Compound (1-217)>
[0297] In Example 14, 4-(2-naphthyl)aniline was replaced with 4'-(2-phenyl-benzoxazol-6-yl)biphenyl-4-yl-amine, and the same reaction was carried out. After collecting the solid, it was purified by recrystallization with chlorobenzene to obtain 5.4 g of a yellow powder of compound (1-217) (yield: 53%).
[0298]
[0299] The structure of the obtained yellow powder was identified using NMR.
[0300] use 1 H-NMR (CDCl3) detected the signals of the following 34 hydrogen atoms.
[0301] δ(ppm)=8.29(2H), 7.84(2H), 7.79(4H), 7.72(4H), 7.66(1H), 7.61(2H), 7.56(5H), 7.52(2H), 7.32-7.20(10H), 6.95(2H).
[0302] [Example 27]
[0303] <Synthesis of Compound (1-218)>
[0304] In Example 14, 4-(2-naphthyl)aniline was replaced with 4-(2-phenyl-benzothiazol-6-yl)aniline, and the same reaction was carried out. After collecting the solid, it was purified by crystallization with chlorobenzene to obtain 7.6 g of a yellow powder of compound (1-218) (yield: 80%).
[0305]
[0306] The structure of the obtained yellow powder was identified using NMR.
[0307] use 1 H-NMR (CDCl3) detected the signals of the following 30 hydrogen atoms.
[0308] δ(ppm)=8.12(4H), 7.79(4H), 7.73(1H), 7.61(2H), 7.57(2H), 7.51(5H), 7.32-7.19(10H), 6.95(2H).
[0309] [Example 28]
[0310] <Synthesis of Compound (1-219)>
[0311] 5.2 g of 4-(naphthyl-1-yl)aniline, 160 mL of toluene, 16.6 g of 2-(4'-chlorobiphenyl)benzofuran, 6.8 g of sodium tert-butoxide, 0.9 g of tris(dibenzylacetone)dipalladium, and 0.8 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added to a nitrogen-purified reaction vessel, and the mixture was stirred under reflux overnight. After cooling to room temperature, methanol was added, and the solid was collected by filtration. The resulting solid was purified by crystallization using monochlorobenzene and acetone to give 11.1 g of a yellow powder of compound (1-219) (yield: 63%).
[0312]
[0313] The structure of the obtained yellow powder was identified using NMR.
[0314] use 1 H-NMR (THF-d8) detected the signals of the following 37 hydrogen atoms.
[0315] δ(ppm)=8.02(1H), 7.98(4H), 7.91(1H), 7.85(1H), 7.77(4H), 7.70(4H), 7.58(2H), 7.53-7.44(8H), 7.31(6H), 7.28-7.20(6H).
[0316] [Example 29]
[0317] Synthesis of Compound (1-220)
[0318] 30.0 g of 4-(2-naphthyl)aniline, 300 mL of toluene, 37.4 g of 2-(4-bromophenyl)benzofuran, 26.3 g of sodium tert-butoxide, 2.5 g of tris(dibenzylacetone)dipalladium, and 1.7 g of 2,2'-bis(diphenylphosphino)-1,1'-binaphthyl were added to a nitrogen-purified reaction vessel, and the mixture was stirred under reflux overnight. After cooling to room temperature, methanol was added, and the precipitated solid was collected by filtration. The solid was purified by crystallization using a mixed solvent of chlorobenzene and acetone to obtain 39.4 g of a yellow powder of (4-benzofuran-2-yl-phenyl)(4-naphthyl-2-yl-phenyl)amine (yield: 70%).
[0319] 7.5 g of the obtained (4-benzofuran-2-yl-phenyl)(4-naphth-2-yl-phenyl)amine, 80 mL of xylene, 6.1 g of 2-(4'-chlorobiphenyl-4-yl)benzofuran, 3.5 g of sodium tert-butoxide, 0.2 g of tris(dibenzylacetone)dipalladium, and 0.4 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added to a nitrogen-purged reaction vessel and stirred overnight under reflux. After cooling to room temperature, methanol was added, and the precipitated solid was collected by filtration. The obtained solid was purified by crystallization using a tetrahydrofuran / acetone mixed solvent to give 10.6 g of a yellow powder of compound (1-220) (yield: 85%).
[0320]
[0321] The structure of the obtained yellow powder was identified using NMR.
[0322] use 1 H-NMR (CDCl3) detected the following 33 hydrogen signals.
[0323] δ(ppm)=8.05(1H), 7.95-7.86(5H), 7.80-7.75(3H), 7.71-7.68(4H), 7.6 0(4H), 7.56(1H), 7.53-7.46(4H), 7.37-7.21(9H), 7.07(1H), 6.95(1H).
[0324] [Example 30]
[0325] <Synthesis of Compound (1-221)>
[0326] In Example 29, (4-benzofuran-2-yl-phenyl)(4-naphth-2-yl-phenyl)amine was replaced with (4-benzofuran-2-yl-phenyl)(4-dibenzofuran-3-yl-phenyl)amine, and the same operation was performed to obtain 7.4 g of yellow powder of compound (1-221) (yield: 69%).
[0327]
[0328] The structure of the obtained yellow powder was identified using NMR.
[0329] use 1 H-NMR (CDCl3) detected the following 33 hydrogen signals.
[0330] δ(ppm)=8.01-7.93(4H), 7.81-7.78(3H), 7.71(2H), 7.66-7.45(12H), 7.39-7.21(10H), 7.01(1H), 6.96(1H).
[0331] [Example 31]
[0332] <Synthesis of Compound (1-222)>
[0333] In Example 29, (4-benzofuran-2-yl-phenyl)(4-naphth-2-yl-phenyl)amine was replaced with (4-benzofuran-2-yl-phenyl)(4-benzoxazol-2-yl-phenyl)amine, and the same reaction was performed. After collecting the solid, it was purified by crystallization using a mixed solvent of chlorobenzene / acetone, thereby giving 8.0 g of a yellow powder of compound (1-222) (yield: 96%).
[0334]
[0335] The structure of the obtained yellow powder was identified using NMR.
[0336] use 1 H-NMR (CDCl3) detected the signals of the following 30 hydrogen atoms.
[0337] δ(ppm)=8.15(2H), 7.95(2H), 7.83(2H), 7.75(1H), 7.71(2H), 7.66-7.50(7H), 7.38-7.21(12H), 7.07(1H), 6.98(1H).
[0338] [Example 32]
[0339] <Synthesis of Compound (1-223)>
[0340] 5.0 g of (4-benzofuran-2-yl-phenyl)(4-naphthyl-2-yl-phenyl)amine, 50 mL of xylene, 4.3 g of 2-(4'-chlorobiphenyl-4-yl)benzothiophene, 2.4 g of sodium tert-butoxide, 0.2 g of tris(dibenzylacetone)dipalladium, and 0.2 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added to a nitrogen-purified reaction vessel, and the mixture was stirred under reflux overnight. After cooling to room temperature, methanol was added, and the precipitated solid was collected by filtration. The resulting solid was purified by crystallization using a tetrahydrofuran / acetone mixture to give 5.7 g of a yellow powder of compound (1-223) (yield: 67%).
[0341]
[0342] The structure of the obtained yellow powder was identified using NMR.
[0343] use 1 H-NMR (DMSO-d6) detected the following 33 hydrogen signals.
[0344] δ(ppm)=8.24(1H), 8.02-7.94(5H), 7.91-7.77(12H), 7.63(2H), 7.53(2H), 7.43-7.21(11H).
[0345] [Example 33]
[0346] <Synthesis of Compound (1-224)>
[0347] In Example 32, (4-benzofuran-2-yl-phenyl)(4-naphth-2-yl-phenyl)amine was replaced with (4-benzofuran-2-yl-phenyl)(4-dibenzofuran-3-yl-phenyl)amine, and the same operation was performed to obtain 6.6 g of yellow powder of compound (1-224) (yield: 77%).
[0348]
[0349] The structure of the obtained yellow powder was identified using NMR.
[0350] use 1 H-NMR (CDCl3) detected the following 33 hydrogen signals.
[0351] δ(ppm)=8.00(1H), 7.97(1H), 7.84(1H), 7.81-7.78(6H), 7.68-7.56(11H), 7.52(1H), 7.47(1H), 7.38-7.21(10H), 6.95(1H).
[0352] [Example 34]
[0353] <Synthesis of Compound (1-225)>
[0354] In Example 32, (4-benzofuran-2-yl-phenyl)(4-naphth-2-yl-phenyl)amine was replaced with (4-benzofuran-2-yl-phenyl)(4-benzoxazol-2-yl-phenyl)amine, and the same reaction was carried out. After collecting the solid, it was purified by crystallization using a mixed solvent of chlorobenzene / acetone, thereby giving 7.8 g of a yellow powder of compound (1-225) (yield: 91%).
[0355]
[0356] The structure of the obtained yellow powder was identified using NMR.
[0357] use 1 H-NMR (CDCl3) detected the signals of the following 30 hydrogen atoms.
[0358] δ(ppm)=8.15(2H), 7.88-7.77(6H), 7.75(1H), 7.67(2H), 7.64-7.54(5H), 7.52(1H), 7.40-7.21(12H), 6.98(1H).
[0359] [Example 35]
[0360] Synthesis of Compounds (1-72)
[0361] 7.0 g of (4-benzothiophene-2-yl-phenyl)(4-benzothiazol-2-yl-phenyl)amine, 70 mL of toluene, 6.1 g of 2-(7-bromonaphthyl-2-yl)benzothiophene, 2.3 g of sodium tert-butoxide, 0.4 g of tris(dibenzylacetone)dipalladium, and 0.8 g of a 50% (w / v) toluene solution of tri-tert-butylphosphine were added to a nitrogen-purified reaction vessel, and the mixture was stirred under reflux overnight. After cooling to room temperature, methanol was added, and the precipitated solid was collected by filtration. The solid was purified by recrystallization using chlorobenzene to give 7.4 g of a yellow powder of compound (1-72) (yield: 66%).
[0362]
[0363] The structure of the obtained yellow powder was identified using NMR.
[0364] use 1 H-NMR (CDCl3) detected the signals of the following 28 hydrogen atoms.
[0365] δ (ppm)=8.05(1H), 8.01(2H), 7.98(1H), 7.91-7.77(8H), 7.69-7.63(4H), 7.53(1H), 7.49(1H), 7.39-7.26(10H).
[0366] [Example 36]
[0367] For amine compounds represented by general formula (1), the glass transition temperature (Tg) and melting point were determined using a high-sensitivity differential scanning calorimeter (Bruker AXS KK, DSC3100SA). The results are summarized in Table 1.
[0368] [Table 1]
[0369]
[0370] In this way, the amine compound of general formula (1) suitable for use in the organic EL element of the present invention has a glass transition temperature (Tg) of 100°C or higher or no glass transition temperature (Tg) observed, indicating that the film state is stable.
[0371] [Example 37]
[0372] Using an amine compound of general formula (1), an 80 nm thick vapor-deposited film was formed on a silicon substrate. The refractive index n and extinction coefficient k at wavelengths of 450 nm and 750 nm were measured using a spectrophotometer (FILMETRICS F10-RT-UV). Additionally, for comparison, measurements were also performed on the comparative compound (2-1) and Alq3 with the following structural formula (see, for example, Patent Document 6). The results of the refractive index n and extinction coefficient k measurements are summarized in Table 2.
[0373]
[0374] [Table 2]
[0375]
[0376] In this way, the amine compound of general formula (1) suitable for use in the organic EL element of the present invention has a value of 1.85 or higher in the wavelength range of 450 nm or more and 750 nm or less, showing a larger refractive index than Alq3 and comparative compound (2-1) as existing materials. Furthermore, the extinction coefficient shows a low value comparable to Alq3 and comparative compound (2-1) as existing materials. This means that by using the amine compound of general formula (1) suitable for use in the organic EL element of the present invention as the constituent material of the capping layer, an improvement in the light extraction efficiency of the organic EL element can be expected.
[0377] [Example 38]
[0378] Organic EL components such as Figure 18 As shown, the material is fabricated by vapor deposition on an object obtained by pre-forming a reflective ITO electrode as a metal anode 2 on a glass substrate 1, in the following order: hole injection layer 3, hole transport layer 4, light-emitting layer 5, electron transport layer 6, electron injection layer 7, cathode 8, and capping layer 9.
[0379] Specifically, on a glass substrate 1, a 50 nm thick ITO film, a 100 nm thick silver alloy reflective film, and a 5 nm thick ITO film are sequentially deposited as the metal anode 2. The resulting object is ultrasonically cleaned in isopropanol for 20 minutes and then dried on a heating plate heated to 250°C for 10 minutes. Afterward, a 2-minute UV ozone treatment is performed, and the glass substrate with ITO is placed in a vacuum evaporation machine, with the pressure reduced to below 0.001 Pa. Next, to cover the metal anode 2, a binary evaporation process is performed on an electron acceptor (Acceptor-1) and a compound (3-1) of the following structural formula at a evaporation rate ratio of (Acceptor-1):compound (3-1) = 3:97, forming a hole injection layer 3 with a thickness of 10 nm. On this hole injection layer 3, a hole transport layer 4 is formed with a thickness of 140 nm using the compound (3-1) of the following structural formula. On the hole transport layer 4, compound (3-2) and compound (3-3) of the following structural formulas are subjected to binary vapor deposition at a deposition rate ratio of compound (3-2):compound (3-3) = 5:95 to form a light-emitting layer 5 with a film thickness of 20 nm. On the light-emitting layer 5, compound (3-4) and compound (3-5) of the following structural formulas are subjected to binary vapor deposition at a deposition rate ratio of compound (3-4):compound (3-5) = 50:50 to form an electron transport layer 6 with a film thickness of 30 nm. On the electron transport layer 6, lithium fluoride is formed as an electron injection layer 7 with a film thickness of 1 nm. On the electron injection layer 7, a magnesium-silver alloy is formed as a cathode 8 with a film thickness of 12 nm. Finally, compound (1-10) of Example 1 is formed as a capping layer 9 with a film thickness of 60 nm. The characteristics of the fabricated organic EL element were measured in the atmosphere at room temperature.
[0380] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0381]
[0382]
[0383] [Example 39]
[0384] In Example 38, compounds (1-34) from Example 2 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0385] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0386] [Example 40]
[0387] In Example 38, compounds (1-7) of Example 3 were used instead of compounds (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0388] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0389] [Example 41]
[0390] In Example 38, compounds (1-29) from Example 4 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0391] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0392] [Example 42]
[0393] In Example 38, compounds (1-32) from Example 5 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0394] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0395] [Example 43]
[0396] In Example 38, compounds (1-33) from Example 6 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0397] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0398] [Example 44]
[0399] In Example 38, compounds (1-35) from Example 7 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0400] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0401] [Example 45]
[0402] In Example 38, compounds (1-37) from Example 8 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0403] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0404] [Example 46]
[0405] In Example 38, compounds (1-39) from Example 9 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0406] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0407] [Example 47]
[0408] In Example 38, compounds (1-87) from Example 10 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, an organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0409] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0410] [Example 48]
[0411] In Example 38, compounds (1-95) from Example 11 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0412] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0413] [Example 49]
[0414] In Example 38, compounds (1-96) from Example 12 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0415] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0416] [Example 50]
[0417] In Example 38, the compound (1-211) of Example 13 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0418] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0419] [Example 51]
[0420] In Example 38, the compound (1-152) of Example 14 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0421] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0422] [Example 52]
[0423] In Example 38, the compound (1-153) of Example 15 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0424] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0425] [Example 53]
[0426] In Example 38, the compound (1-154) of Example 16 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0427] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0428] [Example 54]
[0429] In Example 38, the compound (1-158) of Example 17 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0430] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0431] [Example 55]
[0432] In Example 38, compounds (1-160) from Example 18 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0433] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0434] [Example 56]
[0435] In Example 38, the compound (1-161) of Example 19 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0436] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0437] [Example 57]
[0438] In Example 38, the compound (1-166) of Example 20 was used instead of the compound (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0439] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0440] [Example 58]
[0441] In Example 38, compounds (1-212) from Example 21 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0442] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0443] [Example 59]
[0444] In Example 38, compounds (1-213) from Example 22 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0445] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0446] [Example 60]
[0447] In Example 38, compounds (1-216) from Example 25 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0448] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0449] [Example 61]
[0450] In Example 38, compounds (1-217) from Example 26 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0451] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0452] [Example 62]
[0453] In Example 38, compounds (1-218) from Example 27 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0454] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0455] [Example 63]
[0456] In Example 38, compounds (1-219) from Example 28 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0457] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0458] [Example 64]
[0459] In Example 38, compounds (1-220) from Example 29 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0460] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0461] [Example 65]
[0462] In Example 38, compounds (1-221) from Example 30 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0463] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0464] [Example 66]
[0465] In Example 38, the compounds (1-222) of Example 31 were used instead of the compounds (1-10) of Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0466] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0467] [Example 67]
[0468] In Example 38, compounds (1-223) from Example 32 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0469] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0470] [Example 68]
[0471] In Example 38, compounds (1-224) from Example 33 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0472] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0473] [Example 69]
[0474] In Example 38, compounds (1-225) from Example 34 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0475] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0476] [Example 70]
[0477] In Example 38, compounds (1-72) from Example 35 were used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0478] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0479] [Comparative Example 1]
[0480] For comparison, in Example 38, Alq3 was used instead of compounds (1-10) from Example 1 as the capping layer 9. Otherwise, an organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0481] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0482] [Comparative Example 2]
[0483] For comparison, in Example 38, comparative compound (2-1) was used instead of compound (1-10) in Example 1 as the capping layer 9. Otherwise, the organic EL element was fabricated under the same conditions. The characteristics of the fabricated organic EL element were measured in air at room temperature.
[0484] The results of measuring the light emission characteristics of the fabricated organic EL element under a DC voltage are summarized in Table 3.
[0485] The results of the device lifetime measurements using the organic EL devices prepared in Examples 38-70 and Comparative Examples 1-2 are summarized in Table 3. Device lifetime is measured at 10 mA / cm². 2 The time it takes for the light to decay to 95% of the initial brightness when driven by a constant current (95% decay) is measured.
[0486] [Table 3]
[0487]
[0488] As shown in Table 3, regarding a current density of 10 mA / cm² 2 The driving voltage of Comparative Examples 1-2 is almost the same as that of Examples 38-70, which use the amine compound of general formula (1) as a capping layer. In contrast, the brightness, luminous efficiency, power efficiency, and element life of Examples 38-70 are significantly improved compared to the elements of Comparative Examples 1 and 2. This indicates that the amine compound of general formula (1) suitable for use in the organic EL element of the present invention is a suitable material for the capping layer, and the high refractive index of the capping layer can significantly improve the light extraction efficiency of the organic EL element.
[0489] Industrial availability
[0490] The amine compound of general formula (1) suitable for use in the organic EL element of the present invention has a high refractive index, which can significantly improve light extraction efficiency and has a stable film state. Therefore, it is excellent as a compound suitable for use in organic EL elements. Organic EL elements made using the amine compound of general formula (1) suitable for use in the organic EL element of the present invention can achieve high efficiency. In addition, by using the amine compound of general formula (1) which does not have absorption in the respective wavelength regions of blue, green and red and is suitable for use in the organic EL element of the present invention, it is particularly suitable for situations where it is desired to display images with good color purity, clarity and brightness. For example, it can be applied in household electrical appliances and lighting applications.
[0491] Explanation of reference numerals in the attached figures
[0492] 1. Glass substrate
[0493] 2 Metal Anode
[0494] 3. Hole injection layer
[0495] 4 Hole transport layer
[0496] 5. Light-emitting layer
[0497] 6. Electron transport layer
[0498] 7 Electron Injection Layer
[0499] 8 Cathode
[0500] 9. Covering layer
Claims
1. An organic electroluminescent element, comprising at least an anode electrode, a hole transport layer, a light-emitting layer, an electron transport layer, a cathode electrode, and a capping layer in sequence, wherein, The coating layer contains an amine compound represented by the following general formula (1). (1) In formula (1), Ar1 and Ar2 may be chosen to be the same or different from each other, representing the structure shown in the following general formula (A) with either R5 or R6 as the bonding site of a monovalent group; Ar3 represents the structure shown in the following general formula (A) with either R5 or R6 as the bonding site of a monovalent group, a substituted or unsubstituted aromatic hydrocarbon group, or a substituted or unsubstituted aromatic heterocyclic group; L1 and L2 may be chosen to be the same or different from each other, representing a substituted or unsubstituted divalent group of an aromatic hydrocarbon with 6 to 18 cyclic carbon atoms; L3 represents a substituted or unsubstituted divalent group of an aromatic hydrocarbon with 6 to 18 cyclic carbon atoms, or a single bond. (A) In formula (A), X represents an oxygen atom or a sulfur atom; R1 to R4 may be the same or different from each other, representing a hydrogen atom, a deuterium atom, a fluorine atom, a chlorine atom, a cyano group, a nitro group, an alkyl group with 1 to 6 carbon atoms that may be substituented, a cycloalkyl group with 5 to 10 carbon atoms that may be substituented, an alkenyl group with 2 to 6 carbon atoms that may be substituented, an alkoxy group with 1 to 6 carbon atoms that may be substituented, a cycloalkoxy group with 5 to 10 carbon atoms that may be substituented, a substituted or unsubstituted aromatic hydrocarbon group, a substituted or unsubstituted aromatic heterocyclic group, or a substituted or unsubstituted aryloxy group, wherein any of R1 to R4 bonded to the same benzene ring The ring is formed by mutual bonding of a single bond, a substituted or unsubstituted methylene group, an oxygen atom, or a sulfur atom; either R5 or R6 is a linking group serving as the bonding site, and it represents a hydrogen atom, a deuterium atom, a fluorine atom, a chlorine atom, a cyano group, a nitro group, an alkyl group with 1 to 6 carbon atoms that is optionally substituent, a cycloalkyl group with 5 to 10 carbon atoms that is optionally substituent, an alkenyl group with 2 to 6 carbon atoms that is optionally substituent, an alkoxy group with 1 to 6 carbon atoms that is optionally substituent, a cycloalkoxy group with 5 to 10 carbon atoms that is optionally substituent, a substituted or unsubstituted aromatic hydrocarbon group, or a substituted or unsubstituted aromatic heterocyclic group.
2. The organic electroluminescent element according to claim 1, characterized in that, The general formula (A) is the structure shown in the following general formula (A-1). (A-1) In formula (A-1), the dashed part is the bonding part, and X, R1~R4, and R6 are defined as in the general formula (A).
3. The organic electroluminescent element according to claim 1, characterized in that, The general formula (A) is the structure shown in the following general formula (A-2). (A-2) In formula (A-2), the dashed part is the bonding part, and X, R1~R5 are defined as in the general formula (A).
4. The organic electroluminescent element according to claim 1, characterized in that, In the general formula (1), L1 and L2 are divalent groups formed by removing two hydrogen atoms from unsubstituted benzene, divalent groups formed by removing two hydrogen atoms from unsubstituted naphthalene, or divalent groups formed by removing two hydrogen atoms from unsubstituted biphenyl.
5. The organic electroluminescent element according to claim 1, characterized in that, The amine compound represented by general formula (1) is represented by the following general formula (1-a). (1-a) In formula (1-a), X, Ar3, L3, R1~R4, and R6 are defined as in general formula (1) and general formula (A).
6. The organic electroluminescent element according to claim 1, characterized in that, The amine compound represented by general formula (1) is represented by the following general formula (1-b). (1-b) In formula (1-b), X, Ar3, L3, R1~R5 are defined as in general formula (1) and general formula (A).
7. The organic electroluminescent element according to any one of claims 1 to 6, wherein, The thickness of the covering layer is in the range of 30nm to 120nm.
8. The organic electroluminescent element according to any one of claims 1 to 6, wherein, The refractive index of the coating layer is 1.85 or higher in the range of light wavelengths above 450 nm and below 750 nm.
9. An electronic device, characterized in that, It comprises the organic electroluminescent element as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Compound for organic el element and organic el element
JP1996048656A
Organic electroluminescence element
WO2013038627A1
Compound for organic optoelectric device, organic light emitting diode comprising same, and display apparatus comprising organic light emitting diode
WO2014104500A1
Triamine derivative and organic electroluminescent device thereof
CN111205237A
Tribenzazole amine derivative and organic electroluminescent device comprising same
WO2020122359A1